The Essence of The Ummah Principle: Islam and The Foundation of Inclusive Social Systems - Wang, Yongbao (Afkar: Jurnal Akidah dan Pemikiran Islam, 2024)
This article explores the essence of the ummah principle in the geopolitical dissemination of Islam during the time of the Prophet Muhammad (PBUH). This is achieved through an analysis of Qur’anic verses related to human nature and worldview, alongside examining the resulting international social pattern of “Unity + Plurality” as reflected in the Sunnah, utilizing both inductive and deductive methodologies. The research yields three key conclusions: 1. The Qur’anic principle of “no compulsion in religion” is a fundamental policy guideline for Islamic countries and governments throughout history, fostering harmonious coexistence among diverse communities. 2. Islam provides a successful model of “human rights + social standards” through the dualism of “metaphysics + physics,” integrating the spiritual and material dimensions of its teachings organically. 3. Islam constructs an inclusive social system rooted in justice, ensuring its functionality through the principles of “de-sectarianism,” “de-clanalism,” and “de-racism.”.